Training of rowers before world championships - Steinacker, J. M.; Lormes, W.; Lehmann, M.; Altenburg, D. (Medicine & Science in Sports & Exercise, 1998)
In rowing, static and dynamic work of approximately 70% of the body's muscle mass is involved for 5.5 to 8 min at an average power of 450 to 550 W. In high load training phases before World Championships, training volume reaches 190 min·d-1, of which between 55 and 65% is performed as rowing, and the rest is nonspecific training like gymnastics and stretching and semispecific training like power training. Rowing training is mainly performed as endurance training, rowing 120 to 150 km or 12 h·wk-1. Rowing at higher intensities is performed between 4 and 10% of the total rowed time. The increase in training volume during the last years of about 20% was mainly reached by increasing nonspecific and semispecific training. The critical borderline to long-term overtraining in adapted athletes seems to be 2 to 3 wk of intensified prolonged training of about 3 h·d-1. Sufficient regeneration is required to avoid overtraining syndrome. The training principles of cross training, alternating hard and easy training days, and rest days reduce the risk of an overtraining syndrome in rowers.